Effectiveness of Cardiac Rehabilitation Instructional Program on Health-related Quality of Life for Patients Undergone Coronary Artery Bypass Graft Surgery - Isam, Safad Riyadh; Hassan, Hakima Shakir (Iraqi National Journal of Nursing Specialties, 2023)
Objective(s): evaluation of effectiveness of cardiac rehabilitation instructional program on health-related quality of life and to find out the relationship between health-related quality of life and patient’s socio-demographic and clinical characteristics. Methodology: A descriptive study design was carried out from 8th August, 2022 to 10th January, 2023. A non-probability purposive sample of (50) patients undergone coronary artery bypass graft surgery at Iraqi center for heart diseases using pre-experimental design. The data were collected by direct interview with sample using questionnaire composed of three parts: part (1) Socio-demographic and clinical characteristics which included 11 items. Part (2) Knowledge related to the cardiac rehabilitation program, which includes 20 items, and part (3) Health-related quality of life (HRQoL) which included 5 domains. Data analysis was carried out through using (SPSS) package ver.23. Descriptive and inferential data were analyzed by using: frequency, percentage, mean of score, standard deviation and paired t test. Results: The findings of the study showed that most of patients (66%) were males, (38%) were within the age group (48- 57 years). Patient’s knowledge about cardiac rehabilitation before applying the program were poor in most items, while their knowledge increased after applying the program. Conclusions: The study concluded that there were high significant statistical differences between patient’s knowledge about cardiac rehabilitation program and their HRQoL. Also there is significant positive relationship between HRQoL and patient’s socio-demographic and clinical characteristics. Recommendations: The study recommended the urge need for establishing cardiac rehabilitation programs within the Iraqi cardiac hospitals and centers and applying of rehabilitation programs that focus on improving HRQoL.